Cadernos do Ceis 20 N.º 26: Monumentos do Salazarismo. Curta-metragem retrospetiva - Luís Miguel Correia (Cadernos do Ceis20, 2019)
In the recent research work entitled Monuments, Territory and Identity in Estado Novo we have found that a specific political ideology materialised in the Portuguese spatial organisation based on the definition of a project towards the consciousness of a legacy, an unchallenged strategy devised in the early revival of a Portugueseness defended by the regime led by António de Oliveira Salazar. The notion of Estado Novo would thus be presumably seen as a personal programme seriously committed to nationalist and anti-democratic convictions, projected and sanctioned in a new Constitution responsible for imposing a tendentially totalitarian power. However, due to a number of episodes and facts surrounding the Dictatorship period, such a plan for Portugal was implemented across the land through many and varied works and transformations, which certainly shaped the unmistakable images of the Salazarist Nation. They were known as portraits of Portugueseness, however, as we have found, they not only highlighted those much desired nationalist and regionalist features, but also revealed an international, modern, allegedly illegitimate and forbidden character. The campaigns for the reintegration of national monuments implemented under official technical guidance, which expressly ordered that all old and historical structures had to be returned to their original state, supported the required general aspect and fascistic plans from the North to the South of the territory. The energetic propaganda activity carried out in the first two decades by the Diário de Notícias special delegate, António Ferro, allowed the Portuguese people, and hopefully the world, to idealise about the fairy tale homeland that was believed to be under (re)construction. The ambition was to domesticate everyone's views of Portugal. To that end, commemorations, exhibitions, publications, awards and many other events were organised to disclose and popularise such an ideal. While the cinema, on a smaller scale, was not one of those privileged instruments of indoctrination, it nevertheless reproduced some frames that represented well the animated version of national life, especially through various documentaries on everyday life in the countryside, or the unparalleled history of monuments. Our purpose takes that line to uncover how this industry was appropriated for the sake of the irreproachable ideological myths mustered by the Estado Novo, and how the national monuments portrayed the idea of being Portuguese on canvas. This short-film retrospective of Salazarist Monuments consists of a total of fourteen documentaries shown at Cinemateca Portuguesa.